VALIDASI MODEL PEMBELAJARAN PERSONALIZED SYSTEM FOR INSTRUCTION DALAM MATERI PEMBELAJARAN PERMAINAN BOLA BASKET - Musrie Harto; Agi Ginanjar; Riki Ramadhan (STKIP Subang, 2026)
This study aimed to validate the Personalized System for Instruction (PSI) learning model program for teaching the one-hand set shoot technique in basketball. The study employed a descriptive quantitative research method. The population consisted of all eighth-grade students of SMP Bintang Sembilan Kedokan Bunder, while the sample was selected using a purposive sampling technique. The research instrument was a PSI learning program designed based on the characteristics and principles of the Personalized System for Instruction model. Data were collected through validation sheets used to assess the feasibility of the learning program and were analyzed using SPSS version 23. The results showed a mean score of 12.0000 with a standard deviation of 6.04743. The reliability test using Cronbach’s Alpha yielded a coefficient of 0.500, indicating a moderate level of reliability. These findings suggest that the PSI learning model program for the one-hand set shoot technique in basketball has an adequate level of feasibility and can be used as an alternative instructional program in physical education learning.